Glypican‐1 as a target for fluorescence molecular imaging of bladder cancer. (8th September 2021) - Polikarpov, Dmitry M; Campbell, Douglas H; Zaslavsky, Alexander B; Lund, Maria E; Wu, Angela; Lu, Yanling; Palapattu, Ganesh S; Walsh, Bradley J; Zvyagin, Andrei V; Gillatt, David A
Abstract : Objectives: To investigate whether anti‐glypican‐1 antibody Miltuximab conjugated with near‐infrared dye IRDye800CW can be used for in vivo fluorescence imaging of urothelial carcinoma. Methods: The conjugate, Miltuximab‐IRDye800CW, was produced and characterized by size exclusion chromatography and flow cytometry with glypican‐1‐expressing cells. Balb/c nude mice bearing subcutaneous urothelial carcinoma xenografts were intravenously injected with Miltuximab‐IRDye800CW or control IgG‐IRDye800CW and imaged daily by fluorescence imaging. After 10 days, tumors and major organs were collected for ex vivo study of the conjugate biodistribution, including its accumulation in the tumor. Results: The intravenous injection of Miltuximab‐IRDye800CW to tumor‐bearing mice showed its specific accumulation in the tumors with the tumor‐to‐background ratio of 12.7 ± 2.4, which was significantly higher than that in the control group (4.6 ± 0.9, P  < 0.005). The ex vivo imaging was consistent with the in vivo findings, with tumors from the mice injected with Miltuximab‐IRDye800CW being significantly brighter than the organs or the control tumors. Conclusions: The highly specific accumulation and retention of Miltuximab‐IRDye800CW in glypican‐1‐expressing tumors in vivo shows its high potential for fluorescence imaging of urothelial carcinoma and warrants its further investigation toward clinical translation.